2017
DOI: 10.1038/srep44563
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of red blood cell aggregates in bifurcating microscale flows

Abstract: Microvascular flows are often considered to be free of red blood cell aggregates, however, recent studies have demonstrated that aggregates are present throughout the microvasculature, affecting cell distribution and blood perfusion. This work reports on the spatial distribution of red blood cell aggregates in a T-shaped bifurcation on the scale of a large microvessel. Non-aggregating and aggregating human red blood cell suspensions were studied for a range of flow splits in the daughter branches of the bifurc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 47 publications
0
53
0
Order By: Relevance
“…F* = F Daughter / F Parent ) was introduced for each aggregate size A*examined in the study (1 to 7) and plotted against the normalized flow ratio Q*. Figure 4a shows the edge area distribution in the parent branch for a flow ratio Q* of ~ 0.1 as reported in Kaliviotis et al [15]. The RBC aggregation phenomenon causes distinct changes in the microstructure of the fluid and this is reflected in the statistics of the data in Figure 4a (the distribution is left-truncated at 0.5 for the purpose of noise reduction).…”
Section: Aggregate Size Flux Calculationmentioning
confidence: 95%
See 4 more Smart Citations
“…F* = F Daughter / F Parent ) was introduced for each aggregate size A*examined in the study (1 to 7) and plotted against the normalized flow ratio Q*. Figure 4a shows the edge area distribution in the parent branch for a flow ratio Q* of ~ 0.1 as reported in Kaliviotis et al [15]. The RBC aggregation phenomenon causes distinct changes in the microstructure of the fluid and this is reflected in the statistics of the data in Figure 4a (the distribution is left-truncated at 0.5 for the purpose of noise reduction).…”
Section: Aggregate Size Flux Calculationmentioning
confidence: 95%
“…These patterns can be identified with edge detection algorithms. It was shown that these iso-intensity areas increase almost linearly with the number of RBCs per aggregate for small aggregates of up to 15 RBCs per aggregate [14,15]. The detection algorithm is briefly described below.…”
Section: Rbc Aggregate Size Characterisationmentioning
confidence: 99%
See 3 more Smart Citations